A limit theorem for mixing processes subject to rarefaction. II - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
The limit theorem proved in the first part of this paper is applied to the well-known schemes of processes subject to rarefaction arising in queuing theory, mathematical biology, and in problems for counters.